Methods for ensuring stability of operating conditions of an electric power system with distributed generation plants - Iliev, Iliya; Kryukov, Andrey; Bulatov, Yuri; Suslov, Konstantin; Beloev, Ivan; Valeeva, Yuliya (Institute of Advanced Engineering and Science, 2025)
Modern electric power systems (EPSs) experience an increase in the number of distributed generation plants. These plants can be located far from the center of consumption, which